PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI HIDROLISIS GARAM DI MA PATRA MANDIRI - Indah M Putri; Hartatiana Hartatiana; Resti T Astuti (Orbital: Jurnal Pendidikan Kimia, 2019)
The purpose of this research are determining the effect of discovery learning models on science process skills and determining the student’s activities by applying discovery learning models in the experimental class and conventional learning in the control class. In this research, the writer applied quasi experimental design with non-equivalent control group design. For the sampling method, the writer used random sampling technique. XI MIA 1 with a total of 39 students as experimental design class and XI MIA 2 with a total of 40 students as a control class. Data collection used test techique, there are 10 multiple choice questions of science process skills. While, non-test technique used observation sheet of science process skills. The result of students’ science process skills analysis test from the t test with the posttest result obtained sig. (2-tailed) of 0.003 < 0.05. Based from the explanation. It can be concluded that there is an effect of the discovery learning model on the students’ science process skills in the salt hydrolysis material at MA Patra Mandiri. The results of the observation sheet obtained a percentage of 77% for the experimental class and 71% for the control class. So that science process skills through discovery learning models in salt hydrolysis material at MA Patra Mandiri showed a good criteria.